Determination of absorbed dose of Palladium-103 radiation sources in prostate brachytherapy using the Monte Carlo method - Effendi, Mukhtar; Nabila, Hafsyah Putri; wihantoro, wihantoro; Haryadi, Aris (Journal of Physics: Theories and Applications, 2023)
Prostate cancer is one type of cancer that can be treated with the Brachytherapy Technique. Brachytherapy is a cancer therapy method by implanting radioactive nuclei through electromagnetic radiation from radioactive material placed near the tumor or cancer. The optimal number of implants of Palladium-103 radioactive source needs to be known to ensure the safety level before performing the therapy. The stages carried out in the research include modeling radiation sources and inhomogeneous phantoms around cancer, running the program, and processing the running data. The value of radiation absorbed dose based on the interaction of photons on organs can be obtained using the tally code *f8 in the MCNPX user code input. Based on the research results, the absorbed dose value received by each organ was successfully obtained. In addition, the variation of the implanted Palladium-103 radiation source had a significant effect on the increase of absorbed dose received by each organ. Sources were varied as 10, 11, 12, 13, 14, 15, and 16 sources, respectively. The greater the number of radiation sources implanted, the greater the absorbed dose value received by each organ.